Justice for everyone : the jurisprudence and legal lives of Brenda Hale / edited by Rosemary Hunter, University of Kent, Erika Rackley, University of Kent. - Hunter, Rosemary C.; Rackley, Erika (Cambridge University Press, 2022)
As the first woman to be appointed President of the UK Supreme Court, Brenda Hale was one of the UK's most high profile and influential judges, and she is among the most powerful women leaders of our time. For almost half a century, she pioneered as an educator, reformer, and decision-maker, leaving a distinct mark on the law and the lives of many. In commemoration of her recent retirement from the Supreme Court, this collection celebrates her long and illustrious career. Organised by thematic chapters and featuring original research from leading academics, judges and lawyers, this book offers a comprehensive account of Lady Hale's achievements and enduring impact. The contributors, many of whom were her peers and colleagues, demonstrate how Hale forged her own path within male-dominated institutions, carved a space for herself and others, and, ultimately, endeavoured to promote justice for everyone.